A Systematic Review and Meta-Analysis of Variant Histology in Urothelial Carcinoma of the Bladder Treated with Radical Cystectomy - Mori, Keiichiro; Abufaraj, Mohammad; Mostafaei, Hadi; Quhal, Fahad; Karakiewicz, Pierre I; Briganti, Alberto; Kimura, Shoji; Egawa, Shin; Shariat, Shahrokh F (The Journal of urology, 2020)
PURPOSE: The currently available evidence regarding the prognostic and clinical significance of each variant histology subtype of urothelial bladder cancer remains scarce. We assessed the prognostic value of variant histology in patients with urothelial carcinoma of the bladder treated with radical cystectomy. MATERIALS AND METHODS: PubMed®, Web of Science™, Cochrane Library and Scopus® databases were searched for articles published before October 2019 according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement. We identified 39 studies comprising 20,544 patients matching our eligibility criteria. RESULTS: Studies were deemed eligible if they compared overall, cancer specific and recurrence-free survival in patients with urothelial carcinoma of the bladder with and without variant histology. Formal meta-analyses were performed for these outcomes. Variant histology was associated with worse cancer specific (pooled HR 1.37, 95% CI 1.24-1.50), overall (pooled HR 1.44, 95% CI 1.26-1.65) and recurrence-free survival (pooled HR 1.32, 95% CI 1.20-1.45). Subgroup analyses demonstrated that "micropapillary" (pooled HR 1.20, 95% CI 1.02-1.41), "plasmacytoid" (pooled HR 2.03, 95% CI 1.17-3.52) and "small cell" variant histology (HR 3.32, 95% CI 1.98-5.59) were also associated with worse overall survival. CONCLUSIONS: Variant histology in patients with urothelial carcinoma of the bladder is associated with increased risks of disease recurrence as well as cancer specific and overall mortality. Variant histology was independently associated with overall survival in the "micropapillary," "plasmacytoid" and "small cell" subgroups. Variant histology should be integrated into prognostic tools to guide risk stratification, treatment planning and patient counseling. However, caution should be exercised in interpreting the conclusions drawn from this study given the limitations, which include the heterogeneity of the population of interest and the retrospective nature of the primary data evaluated.
Keywords: meta-analysis; Humans; karcinom z přechodných buněk; močový měchýř; Cystectomy; lidé; přežití bez známek nemoci; histology; cystectomy; nádory močového měchýře; urinary bladder neoplasms; Urinary Bladder; prognóza; Carcinoma, Transitional Cell; urotel; Disease-Free Survival; Urothelium; lokální recidiva nádoru; Risk Assessment; cystektomie; Urinary Bladder Neoplasms; Neoplasm Recurrence, Local; hodnocení rizik; Prognosis